Model Kesetimbangan Adsorpsi Zat Warna Direct Brown Dengan Menggunakan Abu Terbang (Fly Ash) Batubara - Sudung Sugiarto Siallagan; Rozanna Sri Irianty; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The Increasing use of dyes in various industries causes environmental problems that must be addressed. Various methods have been done to reduce the dye waste, one of which is adsorption. Using of inexpensive and easily obtained adsorbents is one of the considerations in choosing the type of adsorbent used. The purpose of this research was to determine the ability of activated fly ash with HCl by adsorbing Direct Brown dyes at equilibrium with variations in concentration of dyes and adsorption temperature and determining the adsorption equilibrium model. This research was carried out by varying the concentration of dyes (10,20, and 30, ppm) and the adsorption temperature (27, and 37, oC). The result showed that the best temperature of adsorbent for adsorbing Direct Brown at 140 minutes was 37 oC with concentration of dyes 30 ppm with mass of adsorben 2 gram. And 96,59% of adsorption efectiveness. The adsorption mechanism meets the FreundLich isotherm model with a values of R2 equal to 1. The equilibrium curve Qe vs Ce showed that equilibrium model is freunlich model with smallest error correction. Key Words : adsorption, activation, dye waste, fly ash, Direct Brown.